Implementasi Putusan Mahkamah Konstitusi Nomor 92/PUU-X/2012 Terkait Kewenangan Dewan Perwakilan Daerah dalam Pembentukan UndangUndang - Fajar Laksono; Anna Triningsih; Ajie Ramdan; Indah Karmadaniah (Jurnal Konstitusi, 2015)
Why Constitutional Court verdict Number. 92/PUU-X/2012 attractive to serve as an object of research? The main reason is, there is a problem that is visible on   the implementation of the Decision. The problem shown in fact that can be observed after the verdict was pronounced in the plenary session of the Constitutional Court. Up to almost 1 (one) year later, since pronounced in the plenary session, the Constitutional Court also considered yet implemented. This research seeks to express the fact that covers the implementation of Constitutional Court Decision No. 92/PUU-X/2012. Therefore, although more as a normative-doctrinal research and/or prescriptive with the focus of study that leads to the question of “how it should act”, this research is very likely propose another style that touches the issue of  “what happened” and “why it happened”. The purpose of the implementation of this study was to determine and explain about the implementation of the Constitutional Court Number 92/PUU-X/2012, including to identify and explain the obstacles  and difficulties in the implementation of the Constitutional Court Decision No. 92/PUU-X/2012, and find out and explain the legal politics legislation following the Ruling of the Constitutional Court Number 92/PUU-X/2012. In this theoretical framework introduced some basic concepts that are key aspects to strengthen the argument in this study. In this regard, this study uses a few basic concepts, namely: (1) the law not only as a rule (rule) but also behavior (behavior), (2) awareness  and compliance with the law; (3) The strength of binding court decisions, and (4) Due to legal and implementation models court decision.